Citizen Security: A contribution of Implacative and Participative Methodologies - García Ojeda, Mauricio; Zambrano Constanzo, Alba (Revista de Psicología, 2005)
This article reviews the concept of citizen security, proposing that this should be understood in the context of current processes of social exclusion. The management of citizen security that is carried out in the public sphere is based on certain conceptions, which define styles that can be oriented towards the fulfillment of norms and monitoring or be based on the valuation of citizen participation. In consonance with this second style of confronting problems of citizen security, it is proposed that this should be conceived from a wide perspective, based on the normative principles of human development and citizen’s rights and that, therefore, consider that actions undertaken should be integrally articulated, so that they may permit conditions of social exclusion to be solved. To make this viable, it is necessary that the diverse initiatives of citizen security operate from a local level, with emphasis on territory and having the use of implicative and participative methodologies at the base of the actions undertaken. Finally, experiences in Spain and Chile are referenced, connected to the citizen security based on participatory methodologies. Also, reflections are presented on the contribution of implicative methodologies to promote citizenship and the sustainable development of cities.